Hiroshima-75 : nuclear issues in global contexts - Fujiwara, Aya, 1971-; Marples, David R. (Ibidem Press, 2020)
75 years after the United States dropped atomic bombs on Hiroshima and Nagasaki, a group of international scholars offers new perspectives on this event and the history, development, and portrayal of the utilization of atomic energy in military and civilian industries, civil nuclear power, literature and film, and the contemporary world.